Design, synthesis, and biological activity of novel semicarbazones as potent Ryanodine receptor1 inhibitors of Alzheimer's disease. (1st January 2021) - Dai, Baozhu; Ma, Xingxing; Tang, Yadong; Xu, Le; Guo, Su; Chen, Xinyan; Lu, Shitong; Wang, Guangjie; Liu, Yajing
Graphical abstract: Abstract: Ryanodine receptors (RyRs) are important ligand-gated Ca 2+ channels; their excessive activation leads to Ca 2+ leakage in the sarcoplasmic reticulum that may cause neurological diseases. In this study, three series of novel potent RyR1 inhibitors based on dantrolene and bearing semicarbazone and imidazolyl moieties were designed and synthesized, and their biological activity was evaluated. Using a single-cell calcium imaging method, the calcium overload inhibitory activities of 26 target compounds were tested in the R614C cell line, using dantrolene as a positive control. The preliminary investigation showed that compound 12a suppressed Ca 2+ release as evidenced by store overload-induced Ca 2+ release (SOICR) (31.5 ± 0.1%, 77.2 ± 0.1%, 93.7 ± 0.2%) at 0.1 μM, 3 μM and 10 μM, respectively. Docking simulation results showed that compound 12a could bind at the active site of the RyR1 protein. The Morris water-maze test showed that compound 12a significantly improved the cognitive behavior of AD-model mice. Further studies on the structural optimization of this series of derivatives are currently underway in our laboratory.